The improvement in dielectric and ferroelectric performance of PZT-PZN ceramics by thermal treatment - Vittayakorn N. (2014)
Pyrochlore-free lead zirconate titanate - lead zinc niobate ceramics have been systematically investigated in the as-sintered condition as well as after annealing. The ceramics were characterized by dielectric spectroscopy and Sawyer-Tower polarization (P-E) measurements. The powders of Pb[(Zr1/2Ti1/2)(1-x)-(Zn1/3Nb2/3)x]O3, where x = 0.1, 0.3 and 0.5 were prepared using the columbite-(wolframite) precursor method. The general trend seems to indicate that the annealed samples become more normal-ferroelectric-like behavior as opposed to the relaxor-ferroelectric-like behavior observed in the as-sintered state. The as-sintered 0.9PZT-0.1PZN ceramic exhibited weak relaxor-ferroelectric behavior, with a relatively low dielectric constant maximum of 14,000 measured at 1 kHz. Annealing resulted in a transition to normal-ferroelectric-like behavior, a shift in the dielectric maximum temperature from 360 °C to 350 °C, and a dramatic increase in the dielectric constant at 1 kHz to a maximum value of 35,000 for the longer anneal. After thermal annealing at 900 °C for one week a strong enhancement of remanent polarization (Pr) was observed. © 2007 Elsevier B.V. All rights reserved.